2012
DOI: 10.1007/s10750-012-1148-3
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton functional and morpho-functional approach in large floodplain rivers

Abstract: Influence of hydrological characteristics and nutrient concentrations on phytoplankton was investigated in four large rivers (Mura, Drava, Danube and Sava) in the Pannonian ecoregion in Croatia to understand how phytoplankton of rivers can be explained by the ''different functional group approach''. To gain a clearer understanding of the factors that affect river phytoplankton, the present study examined phytoplankton biomass and composition in relationship with physical and chemical parameters assessed in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…In this sense, the absence of FGs as indicators in the rivers was probably due to the high water flow that promotes dispersal stochasticity and prevents to determine the relationship between the environmental conditions and the phytoplankton distribution . Moreover, the hydrodynamics of the rivers difficult the phytoplankton establishment because of the wash-out that increases the biovolume losses (Abonyi et al, 2012;Stanković et al, 2012;Devercelli & O'Farrell, 2013;Fraisse et al, 2013). This study demonstrated that the use of phytoplankton FGs is an alternative to obtain ecological and environments responses in the floodplain since the FGs were efficient indicators of hydrological periods and the environmental conditions in lakes and rivers.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In this sense, the absence of FGs as indicators in the rivers was probably due to the high water flow that promotes dispersal stochasticity and prevents to determine the relationship between the environmental conditions and the phytoplankton distribution . Moreover, the hydrodynamics of the rivers difficult the phytoplankton establishment because of the wash-out that increases the biovolume losses (Abonyi et al, 2012;Stanković et al, 2012;Devercelli & O'Farrell, 2013;Fraisse et al, 2013). This study demonstrated that the use of phytoplankton FGs is an alternative to obtain ecological and environments responses in the floodplain since the FGs were efficient indicators of hydrological periods and the environmental conditions in lakes and rivers.…”
Section: Discussionmentioning
confidence: 79%
“…Whereas the low FG L O biovolume registered in periods with high water-column mixing (dry periods) could be explained by the sensitivity of these organisms to deep (e.g. reservoirs) and prolonged mixing Padisák et al, 2009;Borics et al, 2012). We do not disregard the possibility that the high contribution of FG L O in the rivers could be related to the influence of the upstream reservoirs in the Paraná and Paranapanema Rivers, as the dispersion of organisms from the reservoir can influence the structure in downstream (Bovo-Scomparin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We use two complementary functional approaches: the functional group (FG) concept sensu Reynolds (Reynolds, Huszar, Kruk, Naselli-Flores, & Melo, 2002) and the functional trait (FT) approach (Litchman & Klausmeier, 2008;Weithoff, 2003). Functional approaches have enabled better understanding of complex riverine processes repeatedly, such as river continuum and zonation (Abonyi, Leitão, Lanc ßon, & Padis ak, 2012;Abonyi et al, 2014), floodplain dynamics (Devercelli, 2006; Stankovi c, Vlahovi c, Gligora, V arb ır o, & Borics, 2012;Stevi c, Mihaljevi c, & Spoljari c, 2013) and various aspects of biomass/diversity relationships .…”
mentioning
confidence: 99%